2015
DOI: 10.1371/journal.pone.0125973
|View full text |Cite
|
Sign up to set email alerts
|

Time to First Morning Cigarette and Risk of Chronic Obstructive Pulmonary Disease: Smokers in the PLCO Cancer Screening Trial

Abstract: BackgroundTime to first cigarette (TTFC) after waking is an indicator of nicotine dependence. The association between TTFC and chronic obstructive pulmonary disease (COPD), the third leading cause of death in the United States, has not yet been reported.MethodsWe investigated the cross-sectional association between TTFC and prevalent COPD among 6,108 current smokers in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. COPD was defined as a self-reported diagnosis of emphysema, chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…Little consensus exists on the best measure of nicotine dependence, but research supports that two items from the FTND score, time to first cigarette after waking and cigarettes smoked per day, are strong, valid, reliable predictors of quitting behaviors, which are key indicators of dependence (Baker et al, 2007; Borland et al, 2010; Hyland et al, 2006). Studies also suggest that these two measures are distinct predictors of addiction (Borland et al, 2010; Lessov et al, 2004), chronic obstructive pulmonary disease (Guertin et al, 2015), and lung cancer (Gu et al, 2014), suggesting the possibility that different genetic factors may contribute to urgency to smoke and levels of cigarette consumption. In a sample of over 1000 young adults, Haberstick et al (2007) found that time to first cigarette was the most informative measure of heritable factors from the FTND score.…”
Section: Discussionmentioning
confidence: 99%
“…Little consensus exists on the best measure of nicotine dependence, but research supports that two items from the FTND score, time to first cigarette after waking and cigarettes smoked per day, are strong, valid, reliable predictors of quitting behaviors, which are key indicators of dependence (Baker et al, 2007; Borland et al, 2010; Hyland et al, 2006). Studies also suggest that these two measures are distinct predictors of addiction (Borland et al, 2010; Lessov et al, 2004), chronic obstructive pulmonary disease (Guertin et al, 2015), and lung cancer (Gu et al, 2014), suggesting the possibility that different genetic factors may contribute to urgency to smoke and levels of cigarette consumption. In a sample of over 1000 young adults, Haberstick et al (2007) found that time to first cigarette was the most informative measure of heritable factors from the FTND score.…”
Section: Discussionmentioning
confidence: 99%
“…6 A more complete understanding of the genetics underlying ND is needed, as it could help to predict the likelihood of quitting smoking, withdrawal severity, response to treatment, and health-related consequences. [7][8][9][10] The Fagerström Test for ND (FTND), also called the Fagerström Test for Cigarette Dependence, 11 provides a composite phenotype that captures multiple behavioral and psychological features of ND among smokers. 12 While CPD is associated with key markers of ND, such as cessation likelihood 13 , the FTND conveys additional valuable information by including 5 items in addition to CPD.…”
Section: Introductionmentioning
confidence: 99%
“…Eliane O. Guedes-Aguiar, 1,3,6 Cintia R. Sousa-Gonçalves, 2,3 Laisa L. Paineiras-Domingos, 2,3,6 Eloá Moreira-Marconi, 3,4 Danúbia C. Sá-Caputo, 2,3,6,7 Márcia C. Moura-Fernandes, 3,4 Rogério Rufino, 8 Cláudia Henrique Costa, 8 Redha Taiar 5,3 Mario Bernardo-Filho 3 e o potencial de exacerbação da doença. Metodologia: Indivíduos com diagnóstico de DPOC, com idade ≥ 40 anos, serão distribuídos randomicamente em 4 grupos: grupo controle (GC) que não será submetido aos EVCI, grupo submetido aos EVCI na posição sentada 1 vez por semana (GS1) e 2 vezes por semana (GS2) e grupo submetido aos EVCI na posição agachada 2 vezes por semana (GP2).…”
Section: Effects Of Whole Body Vibration Exercises On Functional Paraunclassified
“…COPD is a chronic inflammatory condition of the airways 1 and one of the major causes of morbidity and mortality in the world. [2][3][4] The reduction of the pulmonary function is an important predictor for this cause, 2,5 and, it is associated with acute attacks such as increased cough, dyspnea and purulent sputum. 6,7 According to the 2010 Global Burden of Disease (GBD) study, COPD was responsible for about 5% of global disability and 5% of total deaths (2.9 million).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation